Beyond Numbers: Embracing the Depth of Qualitative Research in Criminology - Ranaweera, Nishani (International Journal of Qualitative Research, 2024)
This article advocates for the integral role of qualitative research in criminology, emphasizing its capability to delve into the nuanced and complex experiences of outliers, such as criminals and victims, whose behaviors and experiences significantly deviate from societal norms. It argues that traditional quantitative methods, while useful for identifying broad patterns and trends, often fall short in capturing the depth of human behavior and the intricacies of social problems. Qualitative methods, including in-depth interviews, ethnography, and case studies, are presented as essential tools for uncovering the motivations, emotions, and social contexts underlying criminal actions and the impact of crime. The article highlights the limitations of quantitative research in dealing with outliers and the dynamic nature of human behavior, underscoring the importance of qualitative approaches in providing a richer, more contextualized understanding of crime and victimization. Through a series of case studies and methodological discussions, it demonstrates how qualitative research enriches criminological inquiry, offering critical insights that are instrumental for theoretical advancement and the development of effective criminal justice policies. The conclusion calls for an integrated approach to criminological research that values the complementary strengths of both qualitative and quantitative methods, fostering a more comprehensive and nuanced understanding of crime and its impacts on society.